THE USE OF ENGLISH IN TOURISM DESTINATIONS IN BAKKARA VILLAGE HUMBANG HASUNDUTAN REGENCY: A SOCIOLINGUISTIC ANALYSIS - Harmoko S, Samuel (Jurnal Ilmiah Akomodasi Agung, 2025)
The study examines the use of English in tourism contexts within Bakkara VillageHumbangHasundutan Regency, an emerging tourism destination in North Sumatra, Indonesia. The research employs a mixed-methods approach including surveys, interviews, and field observations to investigate how English functions as a lingua franca in tourist-local interactions, signage, promotional materials, and digital platforms. Results indicate varying English proficiency levels among tourism stakeholders, substantial challenges in language acquisition, and adaptive linguistic strategies employed by local tourism actors. The research identifies economic advancement opportunities through enhanced English communication and potential tensions between linguistic globalization and local cultural preservation. The study contributes to knowledge regarding sociolinguistic dimensions of tourism development in rural Indonesian contexts and offers practical implications for language education policy and sustainable tourism planning in Bakkara Village and similar emerging destinations.